2005
DOI: 10.1016/j.jhsb.2005.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Complex Regional Pain Syndrome Type 1 after Fractures of the Distal Radius: A Prospective Study of the Role of Psychological Factors

Abstract: A prospective study was designed to investigate the question "Do patients who develop Complex Regional Pain Syndrome Type 1 (CRPS Type 1) after fracture of the distal radius display different psychological behaviour patterns and/or are more depressive than those who recover uneventfully after this fracture?" Sixty-two patients of mean age 56 years with displaced distal radius fractures were operated on by closed reduction and percutaneous fixation with K-wires. All these patients were examined psychologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 22 publications
0
36
0
5
Order By: Relevance
“…Female gender can be considered a risk factor for CRPS [15,[18][19][20][23][24][25][26] and, since there is a higher incidence in older patients, the postmenopausal status is also related higher incidence of CRPS [14][15][16]21], although this association could be an epiphenomena linked to higher incidence of fractures and others traumas in this population. However, the common factor in many of these risks may be nerve entrapment.…”
Section: Risk Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…Female gender can be considered a risk factor for CRPS [15,[18][19][20][23][24][25][26] and, since there is a higher incidence in older patients, the postmenopausal status is also related higher incidence of CRPS [14][15][16]21], although this association could be an epiphenomena linked to higher incidence of fractures and others traumas in this population. However, the common factor in many of these risks may be nerve entrapment.…”
Section: Risk Factorsmentioning
confidence: 94%
“…Dilek et al [18] also showed that high anxiety was correlated with a higher incidence of CRPS after distal radial fracture. However, others have failed to link anxiety and stress to CRPS [19,20].…”
Section: Risk Factorsmentioning
confidence: 99%
“…[41][42][43] Burada; sıkı alçılar, medyan sinirin basısı, medyan veya ulnar sinir yaralanmaları, distal radyoulnar eklemde stabilite bozukluğu, eşlik eden ulna kırık-ları, KBAS oluşmasına yol açabilir. Atkins ve arkadaşla-rı, kırığın şiddeti ile KBAS gelişme sıklığı arasında ilişki bulamazken, Bickerstaff, ciddi kırıklarda KBAS oluşu-munun daha fazla olduğunu belirtmiştir.…”
Section: Tendon Kopmalarıunclassified
“…La littérature actuelle ne met pas en évidence une origine psychogène ou des traits de personnalité prédisposants dans le SDRC [34,50]. En fait, les patients présentant un SDRC de type 1 présentent les mêmes traits psychologiques et les mêmes taux d'anxiété et de dépression que les patients souffrant de fibromyalgie ou présentant des entorses à répétition [30].…”
Section: éValuation Psychologiqueunclassified